A STUDY ON INVESTOR’S PERCEPTION TOWARDS MUTUAL FUNDS IN INDIA (Journal of Pharmaceutical Negative Results, 2022)
Mutual funds have been the subject of inquiry and investigation by academics, researchers, and professionals in the field of finance. It is essential to the growth of the mutual fund industry that investors have a widespread readiness to accept mutual funds as a solid investment. Investors come from a wide range of socioeconomic backgrounds, and they also differ in terms of the rates of return they anticipate earning and the amount of risk they are ready to face. It is quite difficult to produce products that may fulfill the requirements of investors if one does not first determine the demographic and economic characteristics of these individuals. By analyzing the level of risk an investor is willing to take, one may infer the patterns of asset allocation they will use. When investing in mutual funds, it is essential to determine the factors and considerations that influence the investment decisions made by investors. The track records of mutual fund schemes are formed via the use of periodical performance evaluations. These reviews also act as an aggressive marketing technique for the purpose of obtaining cash from individual investors. The following are the objectives of the study to study the perception of the investors towards the mutual fund and to analyze the investors’ behaviour towards mutual funds. The study is qualitative in nature carried out in during the month of August 2022. To understand the investors’ perception towards the mutual funds, 250 sample respondents having investment in the mutual funds are purposively selected. The information is collected through Google forms and analyzed with the help of SPSS.